On the relative abundance and distribution of sperm whales (Physeter macrocephalus) and killer whales (Orcinus orca) in the Falkland Islands longline fishery - Yates , Oliver; Brickle, Paul (J. Cetacean Res. Manage., 2023)
The relative abundance and distribution of sperm whales (Physeter macrocephalus) and killer whales (Orcinus orca) in the Falkland Islands Conservation Zone was investigated by the analyses of scientific observer records from longline fishing vessels between 2002 and 2004. Thematic maps were created of observed spatial and temporal fishing effort and whale sightings. These suggested that killer whales were restricted to the northeast of the zone, whereas sperm whales were present throughout the east along the 1,000m depth-contour. A likelihood ratio test showed sperm whales to be relatively more abundant in the north and south of the zone than in the middle region (p<0.01). Group size and distribution is discussed relative to monthly fishing effort and temporal analysis of sightings considered. 32.4% of observed stations had sperm whales present but no significant difference was found between catches with whales present and catches with no whales present (p=0.8743, t=0.1598, df=25).